Uso de elementos finitos estendidos para a modelagem computacional da fratura de material refratário submetido ao método da cunha - Mendonça, Guilherme da Cunha (Universidade Federal de São Carlos, 2023)
Fracture mechanics must be considered in the structural design of ceramic components, especially for refractory materials that are commonly susceptible to cracking due to high temperature variations in their applications. The fracture of refractories can be analyzed through mechanical tests, among them the wedge splitting test (WST), which allows for stable crack growth even in brittle materials. This test was initially proposed to measure the fracture energy of the test specimen, but the crack propagation path can also be analyzed based on field measurements. With a computational simulation, we can estimate crack propagation, provided that the intrinsic parameters of the model are identified and validated with the help of experiments. The X-FEM (eXtended Finite Element Method), available in the software AbaqusTM, was applied to a WST on a commercial silica-aluminous refractory material. The experimental curve of horizontal force as a function of opening displacement at the application of load height was used as a reference for calibrating the parameters of a crack propagation model for the computational simulation of the test. Preliminary validation procedures were carried out for both 2D and 3D models, and to ensure the reliability of the models, mesh convergence analysis and sensitivity analyses of the parameters were performed. After analyzing both models, it was determined that the 2D model was more appropriate for the case study. An optimization process was performed using the software IsightTM to find a response curve that best approximated the experimental results. With the properties optimized by IsightTM, the 2D X-FEM model could represent the fracture behavior of the material with a good approximation compared to the WST simulations that used cohesive elements from the literature.
Validation of the use of extended finite elements for computational modeling of fracture in refractory material submitted to the wedge splitting test
Keywords: Método da cunha; X-fem; Correlação de imagens digitais; Wedge splitting test; Digital image correlation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA